1992
DOI: 10.1111/j.1365-2672.1992.tb01816.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the lactoperoxidase system: reaction kinetics and antibacterial activity using two methods for hydrogen peroxide generation

Abstract: Components of the lactoperoxidase system were measured during incubation in Isosensitest broth, with enzymatic (glucose oxidase, GO) or chemical (sodium carbonate peroxyhydrate, SCP) means to generate H2O2. When low levels of thiocyanate (SCN-) were used in the GO system, H2O2 was detected and lactoperoxidase (LP) was inactivated when SCN- was depleted. With 10-fold higher SCN-, LP remained active and H2O2 was not detectable. The oxidation product of the LP reaction, most likely hypothiocyanite, was present in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…The short-lived bactericidal effect of the system on H. pylori is in agreement with previous reports of studies with other species of bacteria, in which H 2 O 2 was introduced only at the initiation of the reaction [34,35]. SCN À was used at a concentration of 0.66 mM throughout this study.…”
Section: Discussionsupporting
confidence: 75%
“…The short-lived bactericidal effect of the system on H. pylori is in agreement with previous reports of studies with other species of bacteria, in which H 2 O 2 was introduced only at the initiation of the reaction [34,35]. SCN À was used at a concentration of 0.66 mM throughout this study.…”
Section: Discussionsupporting
confidence: 75%
“…It catalyzes the inactivation of a wide range of microorganisms. [1][2][3] The other members of the mammalian peroxidase family include eosinophil peroxidase (EPO), thyroid peroxidase (TPO), and myeloperoxidase (MPO). 4,5 LPO, EPO, and MPO contribute to the nonimmune host defense system by oxidizing halide and pseudohalide ions to produce potent antimicrobial agents.…”
Section: Introductionmentioning
confidence: 99%
“…Even though SCN" in the milk sample used was sufficient to achieve good LPS antimicrobial activity, a higher concentration of SCN" can protect the immobilized enzymes. For instance, Dionysius et al (1992) reported that H 2 O 2 was not detectable in presence of excess SCN". According to those authors (Dionysius et al 1992), lactoperoxidase was inactivated by H 2 O 2 when SCN" was depleted.…”
Section: Catalyst Stabilitymentioning
confidence: 99%